2016
DOI: 10.1038/ijo.2016.229
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric balloon as an adjunct to lifestyle intervention: a randomized controlled trial

Abstract: Intragastric balloon achieved greater short-term weight loss at 3 and 6 months postballoon removal than lifestyle intervention alone. Adverse gastrointestinal events were common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 32 publications
7
94
0
Order By: Relevance
“…Some authors suggested that after three months of treatment, the volumes should be reset to a higher level, given that 80% of weight loss occurs during that interval, after which there is a heightened level of gastric compliance and a diminished effect of early satiety (19,30) . However, there is much divergence of opinion in the literature concerning readjustment (18,31) .…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggested that after three months of treatment, the volumes should be reset to a higher level, given that 80% of weight loss occurs during that interval, after which there is a heightened level of gastric compliance and a diminished effect of early satiety (19,30) . However, there is much divergence of opinion in the literature concerning readjustment (18,31) .…”
Section: Discussionmentioning
confidence: 99%
“…These balloon volume manipulations have produced an impressive percentage of patients that have a successful outcome-79% (297/376) had > 25% EWL in our retrospective series. This is a significant improvement over the results of 6-month, nonadjustable balloons which have reported response rates ( >25% EWL) of 48% and 46.4% in FDA studies [17,18] and 45.6%, 71.4%, 24%, 75%, and 63%,respectively, in several published studies [13,19,[26][27][28].…”
Section: Discussionmentioning
confidence: 67%
“…A total of 16 700 unique studies were initially identified through the database search, out of which 20 met our inclusion/exclusion criteria . These studies reported results of nine interventions: five pharmaceutical products (Alli [over‐the‐counter Orlistat], Xenical [Orlistat], Contrave [Naltrexone‐bupropion], Belviq [Lorcaserin]) and Saxenda [Liraglutide]), two lifestyle modification programmes (Weight Watchers Meetings and Weight Watchers Online), one food replacement and lifestyle programme (Jenny Craig) and one intragastric balloon system (Orbera) manufactured by Apollo Endosurgery, Inc., headquartered in Austin, Texas.…”
Section: Resultsmentioning
confidence: 99%